Turn and zigzag manoeuvres of Delft catamaran 372 using CFD-based system simulation method - Duman, Suleyman; Bal, Sakir (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Special demands in marine applications such as large capacities in transportation and fast deployment in military operations have brought multihull concepts forward. Open deck areas, high stability characteristics, and a wide range of operating speeds are some of the strong sides of these vessels. The fact that few studies have been done on manoeuvring performance predictions of these types of ships has been the main source of motivation in conducting this study. A fast multihull form, Delft Catamaran 372 (DC372), has been selected for computational fluid dynamics (CFD)-based system simulation application. CFD method has been subjected to a verification and validation (V&V) process using the latest solution verification techniques and available comparison data in the literature. The computerized planar motion mechanism (CPMM) approach has been applied to determine all the necessary hydrodynamic derivatives stated in Abkowitz's manoeuvring model. A new approach to analysis of manoeuvring performance of multihull vessels, discrete study of hull components (DSHC), has been introduced for the interpretation of manoeuvring coefficients. The dynamic manoeuvre system simulator (DynaMaSS) in which a waterjet and conventional steering/propulsion units (SPUs) are implemented, has been presented for the 20-degree turning circle (TC20) and 20/20 zigzag (ZZ20) manoeuvre simulations of DC372. The manoeuvring coefficients of DC372 have been determined at a satisfactory level by the CFD method. Successful results and solution strategies have been presented for DC372.
Keywords: Catamaran manoeuvring; Turning circle; Zigzag; CFD; Delft catamaran; Waterjet; SURFACE COMBATANT; PERFORMANCE; PREDICTION; VALIDATION; Engineering; Oceanography